Understanding action control of resistance training among adults. (March 2022) - Rhodes, Ryan E.; Lithopoulos, Alexander
Abstract: Background: Regular muscle and bone strengthening activities through resistance training (RT) have been associated with numerous health benefits, particularly as adults age, yet participation is low. Effective promotion is likely founded on an understanding of theory-based correlates, yet almost all RT research has focused on college-aged convenience samples and employed social cognition models, which do not consider the intention-behavior gap. The purpose of this study was to explore RT from the perspective of the multi-process action control (M-PAC) framework in a large Canadian adult sample. Method: Canadian adults (N = 1338) completed M-PAC measures of reflective (instrumental attitude, affective attitude, perceived capability and opportunity), regulatory (planning and self-monitoring), and reflexive (habit, identity) processes as well as intention to engage in RT at baseline and RT behavior two-weeks later. Results: Three intention-behavior profiles emerged: a) non-intenders who were not active (41.4%), b) unsuccessful intenders who failed to enact their positive intentions (32.9%), and c) successful intenders who engaged in RT (23.5%). A discriminant function analysis ( p < .01) showed that instrumental and affective attitude, perceived opportunity and planning/self-monitoring distinguished between all three intention-behavior profiles, while perceived capability predicted the intention-RT profiles of females but not males ( p < .01). By comparison, identity was particularly important to younger/middle-aged adults than older females ( p < .01), while habit was associated with the intention-RT profiles of older adults but not younger/middle-aged adults ( p < .01). Conclusions: The findings support the importance of considering both intention formation and translation in RT. Behavior change techniques aimed at reflective, regulatory, and reflexive processes appear necessary. Additional considerations of targeting specific constructs by age and sex may maximize the potential effectiveness of RT interventions. Highlights: This study is one of the first explorations of the intention-behavior gap for resistance training. The intention-behavior gap for resistance training was 58%. Predictors of the intention-behavior gap included reflective, regulatory, and reflexive constructs. Perceived capability predicted the resistance training of females but not males. Resistance training identity was particularly important to younger/middle-aged adults.